Implementation of Procedures for Handling Containers Exceeding the Stacking Time Limit (Long Stay) Against Dwelling Time at PT Terminal Petikemas Surabaya - Putra, Andhika Risqullah; Setiono, Beni Agus; Purwiyanto, Didik (Universitas Hang Tuah, 2025)
Dwelling Time is the time required from unloading a container at the port until the container leaves the port. Dwelling Time at the port is a problem that hinders the smooth flow of goods, causes high logistics costs, and reduces competitiveness. This study was conducted because of the problem of high Dwelling Time in several ports in Indonesia. This study covers three processes in Dwelling Time, namely Pre-Clearance, Custom Clearance, and Post-Clearance. The purpose of this study is to analyze the Implementation of Container Handling Procedures that Exceed the Stacking Time Limit (Long Stay) Against Dwelling Time at PT Terminal Petikemas Surabaya. This study uses a qualitative method with a purposive sampling technique. Data were collected through in-depth interviews with data sources. The data analysis methods used include data reduction, data presentation, and data verification and analysis. The results of the study indicate that the main obstacle in Dwelling Time is caused by delays in service users regarding the completeness of documents, which has an impact on increasing the YOR value during the loading and unloading process. Although Dwelling Time does not have a direct impact on export and import activities, the long duration will affect the performance of PT Terminal Petikemas Surabaya and ultimately reduce the company's income.